University of the future - Abdirahman Suleiman, Mohamed; Ahmad Dahlan, Abdul Rahman (Eclat Research Publication, 2016)
The challenges into the university of the future for E-learning not just in Malaysia but around the world appears driven by disruptive change in the forces of technology, to enhance the delivery of lectures to enhance communication between instructors and students, and among students to provide asynchronous access to course materials which threaten to undermine its business model, Public Private administration workers. University across the world have been forced to accommodate this new ELearning technics to ensure its desire mission and vision competitively and respectfully around the world. As a result, the purpose of this paper is to construct an effective future business model canvas the future while addressing a number of challenges in the coming years. This participant will be compose of IIUM students,Student Recruitment Agency. Established on the study, an extra comprehensive business model canvas (BMC) and value proposition design (VPD) were established suitable the future ELearning education. The people of respondents was rather minor due to time control. The results are new practical business model into the future a comprehensive understanding into the in the main valuable to universities, strategy creators, business organizations and students by offering. This study proposals a valuable foundation of data to each party to goods incredible plans for eLearning that meet worldwide wants.